Protecting Livestock from Theileriosis - Rasulov U.I.; A. N. Buronov (Genius Journals, 2021)
It was found that blood-parasitic diseases of cattle are widespread in the regions of the republic and cause great economic damage. Literature data were analyzed. Modern tools and methods for treatment and prevention were recommended.
Keywords: Cattle; tayloriosis; course of the disease; vaccine